Recent Advances in Developing Lanthanide Metal–Organic Frameworks for Ratiometric Fluorescent Sensing - Sun, Tianying; Gao, Yaobin; Du, Yangyang; Zhou, Lei; Chen, Xian (Frontiers in Chemistry, 2021)
Fluorescent probes have attracted special attention in developing optical sensor systems due to their reliable and rapid fluorescent response upon reaction with the analyte. Comparing to traditional fluorescent sensing systems that employ the intensity of only a single emission, ratiometric fluorescent sensors exhibit higher sensitivity and allow fast visual screening of analytes because of quantitatively analyzing analytes through the emission intensity ratio at two or more wavelengths. Lanthanide metal–organic frameworks (LnMOFs) are highly designable multifunctional luminescent materials as lanthanide ions, organic ligands, and guest metal ions or chromophores are all potential sources for luminescence. They thus have been widely employed as ratiometric fluorescent sensors. This mini review summarized the basic concept, optical features, construction strategies, and the ratiometric fluorescent sensing mechanisms of dual-emitting LnMOFs. The review ends with a discussion on the prospects, challenges, and new direction in designing LnMOF-based ratiometric fluorescent sensors.